Reflections on the Beginnings of an Educational Revolution (?) - (:unkn) unknown (My University, 2014)
If you have read through all the chapters in this book you will have encountered reflections and stories from around the world from the 1970s up to the mid-1990s. An analysis of all of these stories, set in very different countries and systems, shows that the revolution can be said to have begun in the late-1970s and early-1980s. The book also describes some significant events into the 1990s and beyond, but does not go much further into this area: that will have to be for another book! Chapters relate to the introduction of computers into schools in Canada, Norway, The Netherlands, Australia, Spain, Ireland, Israel, New Zealand, USA, Finland, UK, Chile, Poland and South Africa.In this chapter we will attempt to draw together themes common to the stories from the previous chapters. Many chapters have dealt with more than one of these themes even though many countries and systems are covered. We will also consider the aspirations and motivations of these pioneering efforts to introduce computers into the classroom and contemplate outcomes at the end of this period.
Keywords: African Research